Too stressed to eat: Investigating factors associated with appetite loss in subordinate rainbow trout. (1st January 2023) - Best, C.; Jennings, K.; Culbert, B.M.; Flear, K.; Volkoff, H.; Gilmour, K.M.
Abstract: Juvenile rainbow trout ( Oncorhynchus mykiss ) form dominance hierarchies in which subordinates experience chronic social stress and suppression of food intake. Here we tested the hypothesis that inhibition of food intake reflects increased expression of anorexigenic (appetite inhibiting) signals and decreased expression of orexigenic (appetite stimulating) signals. Trout were confined in pairs for 1 or 4 days, or were confined in pairs for 4 days and then allowed to recover from social interactions for 2 or 4 days; sham fish were handled identically but held alone. Subordinates did not feed during social interaction and had lower food intake than dominants or shams during recovery. In parallel, plasma cortisol (∼18–26x) and liver leptin ( lep-a1 ) transcript abundance (∼10–14x) were elevated in subordinates during social interaction but not recovery, suggesting that these factors contributed to the suppression of food intake. Fish deemed likely to become subordinate based on inhibition of food intake in response to a mild stressor also showed elevated liver lep-a1 transcript abundance (∼5x). The moderate response in these fish coupled with a correlation between liver lep-a1 and cortisol suggest that stress-induced elevation of cortisol increased liver lep-a1 transcript abundance in subordinate trout, contributing to stress-induced suppression of food intake. Highlights: Subordinate rainbow trout experience chronic stress and suppression of food intake. During social interactions, subordinates had high cortisol levels and liver leptin mRNA. Pre-existing liver leptin mRNA did not explain the high levels in subordinates. Other appetite-regulating signals did not change in subordinate trout. Thus, stress-induced cortisol may increase liver leptin, contributing to appetite loss.